(untitled) (Circe de clásicos y modernos, 2025)
The Arginusae Trial, in which the Athenian assembly tried and sentenced its ten generals to death during the Peloponnesian War, is often considered an exceptional event and even a deviation of the radical democracy. However, a review of archaic sources and heroic poetry demonstrates that this behavior is firmly rooted in a long tradition of popular control whose origins date back to the dawn of the polis and whose earliest expressions we find in various passages of the Iliad and the Odyssey.